Different eras of council housing estates and their neighbourhood formation: the case of Nottingham - Kurtuluş, Ozlem (2025)
This thesis investigates how council housing estates, developed during different historical periods, have influenced neighbourhood formation and the production of lived space. Using Lefebvre’s spatial triad (conceived, perceived, and lived space) as a framework, the study reveals how large-scale social housing projects shape spatial configurations, social interactions, and community dynamics. It also assesses how planning and design decisions have contributed to neighbourhood formation, highlighting the role of housing policies in fostering social cohesion and neighbourhood vitality.